Advances in the chemistry, pharmacological diversity, and metabolism of 20(R)-ginseng saponins - Chaoming Wang; Juan Liu; Jianqiang Deng; Jiazhen Wang; Weizhao Weng; Hongxia Chu; Qingguo Meng (Journal of Ginseng Research, 2020)
Ginseng has been used as a popular herbal medicine in East Asia for at least two millennia. However, 20(R)-ginseng saponins, one class of important rare ginsenosides, are rare in natural products. 20(R)-ginseng saponins are generally prepared by chemical epimerization and microbial transformation from 20(S)-isomers. The C20 configuration of 20(R)-ginseng saponins are usually determined by 13C NMR and X-ray single-crystal diffraction. 20(R)-ginseng saponins have antitumor, antioxidative, antifatigue, neuroprotective, and osteoclastogenesis inhibitory effects, among others. Owing to the chemical structure and pharmacological and stereoselective properties, 20(R)-ginseng saponins have attracted a great deal of attention in recent years. In this study, the discovery, identification, chemical epimerization, microbial transformation, pharmacological activities, and metabolism of 20(R)-ginseng saponins are summarized. Keywords: 20(R)-ginseng saponin, Epimerization, Identification, Metabolism, Pharmacological activity